Inhibition of oxidative stress and gastric emptying as additional mechanisms of antidiabetic activity of Newbouldia laevis - Ikechukwu Sonne Mbagwu; Peter Achunike Akah; Amara Anwuchaepe Ajaghaku; Obiora Celestine Ugwu; Daniel lotanna Ajaghaku (Elsevier, 2021)
The quest to fill the gap in knowledge about the antidiabetic activity of the leaf extract of Newbouldia laevis has inspired further exploration of its possible mechanisms of antidiabetic action. This study investigated inhibitions of oxidative stress and gastric emptying as additional mechanisms of antidiabetic activity of N. laevis. Antidiabetic activity of the ethanol extract was authenticated using a Streptozotocin-Nicotinamide-induced type 2 diabetic model. In vitro antioxidant potentials of the extract and fraction were evaluated using the total phenolic content and DPPH test while in vivo effect determined in CCL4 induced oxidative stress model using Silymarin as standard. The effect of the extracts and fractions on gastric emptying was determined using the extent of non-absorbable phenol red transit through the stomach. Treatment with 400 mg/kg of the extract produced significant (p < 0.05) reduction in blood glucose at the 6th h compared to 0 h, while at 800 mg/kg, significant (p < 0.05) reduction occurred from 4th h post-treatment. Ethyl acetate fraction (EAF) had the best inhibitory effect with IC50 of 35.3 µg/ml and highest phenolic content of 337.9 mg/GAE followed closely by butanol fraction (BF) with IC50 of 51.8 µg/ml and total phenolic content of 331.8 mg/GAE. EAF and BF produced marked inhibition of lipid peroxidation and increase in catalase and superoxide dismutase enzyme activity at 302 and 604 mg/kg. The butanol fraction elicited the highest GE inhibition. Based on these findings, inhibitions of oxidative stress and gastric emptying may be additional mechanisms of antidiabetic activity of N. laevis leaf extract.